In Situ Proteome Profiling and Bioimaging Applications of Small-Molecule Affinity-Based Probes Derived From DOT1L Inhibitors - Zhu, Biwei; Zhang, Hailong; Pan, Sijun; Wang, Chenyu; Ge, Jingyan; Lee, Jun-Seok; Yao, Shao Q. (WILEY-V C H VERLAG GMBH, 2016)
DOT1L is the sole protein methyltransferase that methylates histone H3 on lysine 79 (H3K79), and is a promising drug target against cancers. Small-molecule inhibitors of DOT1L such as FED1 are potential anti-cancer agents and useful tools to investigate the biological roles of DOT1L in human diseases. FED1 showed excellent in vitro inhibitory activity against DOT1L, but its cellular effect was relatively poor. In this study, we designed and synthesized photo-reactive and "clickable" affinity-based probes (AfBPs), P1 and P2, which were cell-permeable and structural mimics of FED1. The binding and inhibitory effects of these two probes against DOT1L protein were extensively investigated in vitro and in live mammalian cells (in situ). The cellular uptake and sub-cellular localization properties of the probes were subsequently studied in live-cell imaging experiments, and our results revealed that, whereas both P1 and P2 readily entered mammalian cells, most of them were not able to reach the cell nucleus where functional DOT1L resides. This offers a plausible explanation for the poor cellular activity of FED1. Finally with P1/P2, large-scale cell-based proteome profiling, followed by quantitative LC-MS/MS, was carried out to identify potential cellular off-targets of FED1. Amongst the more than 100 candidate off-targets identified, NOP2 (a putative ribosomal RNA methyltransferase) was further confirmed to be likely a genuine off-target of FED1 by preliminary validation experiments including pull-down/Western blotting (PD/WB) and cellular thermal shift assay (CETSA).
Keywords: PHOTO-CROSS-LINKERS; KINASE INHIBITORS; HISTONE METHYLTRANSFERASE; TARGET IDENTIFICATION; SELECTIVE INHIBITORS; PARKINSONS-DISEASE; MLL RECOMBINOME; LEUKEMIA-CELLS; SET DOMAIN; METHYLATION